The Effectiveness of Using WhatsApp as a Media in the Process of Memorizing the Qur'an in Integrated Islamic Elementary Schools during the Covid-19 Pandemic - Subagja, Risriyadi; Maryanti, Rina (Jurnal Abdimas Kartika Wijayakusuma, 2022)
The purpose of this study was to determine the level of effectiveness of using WhatsApp in supporting the process of memorizing the Qur'an. To support this research, the researcher uses a quantitative method, with a pre experimental design model because the data collected and the analysis are quantitative. The target of this research is students in the Integrated Islamic Elementary School with a population of 106 people, which is then taken as many as 10 people from grades 4 and 5 for research. The first step in this research is to give a pre-test to students with 10 questions about memorizing the Qur'an using a Yes or No Likert scale. After doing the pre-test, then the process of memorizing the Qur'an was implemented using WhatsApp as the medium. The last step is to do a post-test with the same questions as in the pre-test, then the data from the pre-test and post-test results are tested for effectiveness using the N Gain formula. The results of this study indicate that the use of WhatsApp as a medium in the process of memorizing the Qur'an is not effective. Because, it can be seen from the average Percentage of N Gain that is produced is 26.40 which means it is smaller than 40.00. Therefore, in memorizing the Qur'an, adequate facilities are needed in conducting online learning and often carrying out guidance on procedures for implementing online learning.